Martuccelli, Danilo. Lima and its arenas. Social powers and cultural hierarchies. Lima: Cauces Editores, 2015, 326 pp. - Cánepa, Gisela (2016)
Discusses the conceptual weaknesses of the book Lima and its arenas by D. Martuccelli through a critique of his notions of miscegenation, fusion, hyper-actor individual and regulatory project.